La dimension symbolique du repas dans la dramaturgie néo-hellénique - Thalia Bousiopoulou (Cahiers Balkaniques)
In plays such as P. Matesis’s The sound and D. Dimitriadis The vertigo of animals before the slaughter, the act of eating forms a threshold opened to alterity. In the first case, dinner provokes the reactivation of the ancient myth. In the second case, it brings to light the dangerous commixture of flesh and speech.